Peru's Environmental Kuznets Curve 2010-2020: A Departmental View - Erazo-Camacho, Milton Royer (2024)
The aim of this article is to empirically test the existence of the Environmental Kuznets Curve between economic growth and average temperature using departmental data from Peru during the period 2010-2020. As a result, it was found that the impact of departmental GDP per capita is negative on average temperature, suggesting that a 1% increase in departmental GDP per capita would decrease the average temperature by 1.92% in Peru's regions. These results strongly refute the existence of the Environmental Kuznets Curve hypothesis, suggesting instead that we are facing a U-shaped curve.